Soil C, N and P Stoichiometry of Shrub Communities in Chenier Wetlands in Yellow River Delta, China - Zhao, Y.Y.; Hu, X.M.; Lu, Z.H. (Asian Journal of Chemistry, 2014)
The stoichiometry of C, N, P has improved understanding of nutrient circulation in ecosystems. However, little information is available about coastal wetlands. Here, wetland soil ecological stoichiometric features of carbon, nitrogen and phosphorus in two different shrub communities (Tamarix chinensis and Ziziphus jujube) in chenier of Yellow river delta were studied. The results showed that there was little soil total organic carbon content with large variation. The content of total nitrogen and phosphorus were extremely lacked, which might be two important nutrient limiting factors for these two plant communities. Soil RCN was much higher than regional and global scales, however, RCP and RNP were far below those two scales. The variation of RCN, RCP and RNP were 1.86, 67.62 and 106.32 %, which characterized relatively stable RCN in 0-30 cm soil in this region. By multiple linear regression analysis, the vegetation community type and soil moisture were key factors affecting soil stoichiometric features.